Desenvolvimento embrionário e fetal de catetos (pecari tajacu linnaeus, 1758) - Araújo Júnior, Hélio Noberto de (Universidade Federal Rural do Semi-Árido, 2021)
Given the importance of the information on intrauterine development in tayassuids, the objective of this study was to describe the external morphology of embryos and fetuses of collared peccaries raised in captivity. Two concepts were used for each gestational age and newborns. On the first third of gestation, there is a marked body curvature, brain vesicles, somites, internal organs, crystalline placoid, auricular protrusion, limb buds. At the 25th day post-copulation (dpc), the embryos had a crown-rump length (CCR) of (10.20 ± 0.85 mm), weighing (0.16 ± 0.02 g); at 30 dpc CCR (13.78 ± 0.08 mm), weighing (0.36 ± 0.02 g); and at 40 dpc CCR (22.12 ± 0.04 mm), weighing (1.37 ± 0.02 g). On the second gestational third, fetuses had lost their body curvature, with greater anatomical definition, such as: skeletal formation, external ear, nostrils, eyelids, tactile hair, closure of cranial sutures. In addition, at 50 dpc, the dorsal scent gland and genital tubercle differentiation were visualized, with CCR (59.66 ± 0.66 mm), weighing (12.36 ± 0.79 g); at 60 dpc, CCR (80.12 ± 4.12 mm), weighing (32.74 ± 2.27 g); at 70 dpc, CCR (110.40 ± 1.23 mm), weighing (83.79 ± 3.20 g); at 80 dpc, CCR (137.01 ± 2.06 mm), weighing (187.69 ± 17.20 g); and at 90 dpc, CCR (150.80 ± 4.24 mm), weighing (211.02 ± 10.11 g). In the final third of gestation, the organs were completely formed, with skin darkening, opening of the eyelids, dental eruption, development of the dorsal odorous gland, external sexual organs, and gender attachments. At 100 dpc it presents CCR (156.75 ± 2.33 mm), weighing (257.63 ± 1.65 g); and at 120 dpc CCR (209.65 ± 18.03 mm), weighing (399.40 ± 48.79 g). The neonates, on the other hand, had CCR (266.10 ± 6.22 mm), weighing (913.05 ± 10.82 g). The data made it possible to determine the neonatal growth, allowing a more reliable estimation, considering the utilization of a real gestational age. This study also provides information that may contribute to the adequate reproductive management, and it furthermore aggregates in the use of reproductive biotechnologies of the species
Keywords: Embriogênese; Embriologia; Morfologia; Morfometria; Tayassuidae; Embryogenesis; Embryology; Morphology; Morphometry; Tayassuidae; CIENCIAS AGRARIAS::MEDICINA VETERINARIA